Mesoporous Co3O4 Nanoflakes as an Efficient and Non-Precious Cathode Catalyst for Oxygen Reduction Reaction in Air-Cathode Microbial Fuel Cells - Kumar, Ravinder; Singh, Lakhveer; Zularisam, A. W. (Elsevier, 2017)
Cobalt oxide is well known for its excellent oxygen reduction reaction (ORR) activity, however, its ORR activity can be further improved by synthesizing its porous architecture. Therefore, mesoporous Co 3 O 4 nanoflakes were prepared by a two-step hydrothermal method and were employed as the cathode cata- lyst in a double-chamber microbial fuel cell (MFC) to explore its ORR activity for electricity generation. The electrochemical tests suggested that addition of Co 3 O 4 nanoflakes enhanced the electrocatalytic ac- tivity of the cathode significantly. Besides, the cathode with a higher concentration of Co3O4 nanoflakes (COF-2) showed faster ORR kinetics as compared to the bare cathode. Evidently, COF-2 achieved an ex- change current density of 4.18 mA/cm 2, which was 3.2 times higher as compared to the bare cathode. Consequently, this improved ORR activity increased the power output in MFC. COF-2 obtained a maxi- mum power density of 347 ±7 mW/m 2, which was approximately 8 times higher than the bare cathode. The enhanced ORR activity and improved electric output in the MFC can be attributed to the mesoporous nature of Co 3 O 4 nanoflakes that exposed a higher number of ORR active sites at the cathode surface. Overall, mesoporous Co 3 O 4 nanoflakes proved to be highly efficient and ca. 30 times cheaper than plat- inum, therefore, can be preferred in large-scale MFC applications over other expensive cathode catalysts.